2019
DOI: 10.1111/hex.12938
|View full text |Cite
|
Sign up to set email alerts
|

Parent escalation of care for the deteriorating child in hospital: A health‐care improvement study

Abstract: Objective To evaluate the implementation of an intervention for parents to escalate care if concerned about their child's clinical condition. Design Mixed‐methods health‐care improvement approach guided by the Theoretical Domains Framework. Methods Implementation of the ‘Calling for Help’ (C4H) intervention was informed by previously identified barriers and facilitators. Evaluation involved audit, review of clinical deterioration incidents, interviews and focus groups. Setting Australian specialist paediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…The value of this unique insight was acknowledged, as an additional source of information to assist staff in assessing for, and identifying, deteriorating patients. This finding is consistent with those from paediatric hospitals, where clinicians supported parents’ distinctive knowledge of their child’s baseline health [ 21 ] and capability to detect early and subtle changes of clinical deterioration [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The value of this unique insight was acknowledged, as an additional source of information to assist staff in assessing for, and identifying, deteriorating patients. This finding is consistent with those from paediatric hospitals, where clinicians supported parents’ distinctive knowledge of their child’s baseline health [ 21 ] and capability to detect early and subtle changes of clinical deterioration [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, based on the current data, it is only possible to hypothesise as to what the barriers may be. Apprehensions, differing or negative perceptions, and limitations in the understanding and awareness of some staff in association with consumer escalation are potential examples that correspond with the outcomes of other studies [ 21 , 23 25 ]. Such considerations also link with the wider literature, which has identified that aspects such as staff commitment, understanding, role identity, and confidence all have the potential to impact upon the implementation of hospital-based interventions [ 36 ].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…15,16 How families best engage with clinicians to escalate concerns remains a challenge even after dedicated improvement interventions. [17][18][19] Without an understanding of why, when, and how families of children with neurologic impairment voice concerns, family expertise may remain underleveraged, resulting in poor communication, poor situation awareness, and preventable harm. Our objectives were to develop a comprehensive understanding of how families identify their child' s evolving state of health and communicate changes with the inpatient team.…”
mentioning
confidence: 99%